Fuzzy multiobjective optimization of truss-structures using genetic algorithm - Kelesoglu, Omer (Elsevier Sci Ltd, 2007)
In this paper, a method for solving fuzzy multiobjective optimization of space truss with a genetic algorithm is proposed. This method enables a flexible method for optimal system design by applying fuzzy objectives and fuzzy constraints. The displacement, tensile stress, fuzzy sets, membership functions and minimum size constraints are considered in formulation of the design problem. An algorithm was developed by using MATLAB programming. The algorithm is illustrated on 56-bar space truss system design problem and the results are discussed. (c) 2007 Elsevier Ltd. All rights reserved.
Keywords: multiobjective; fuzzy sets; genetic algorithm; membership function; truss system